Synthesis and Mechanical Properties of Epoxy Composites Reinforced with Phosphazene Microspheres - Zhao, Zhengping; Ji, Jianbing; Yu, Fengying (Asian Journal of Chemistry, 2014)
Using precipitation polymerization to synthesize polycyclotriphosphazene-sulfone microspheres with hexachlorocyclotriphosphazene and 4,4'-sulfonyldiphenol and filled epoxy matrix to prepare composites to study the thermal and mechanical modified mechanisms. Polycyclotriphosphazene-sulfone microspheres has an average particle diameter of 500 nm, the initial decomposition temperature is 457.5 °C and the solid residual rate at 600 °C is 63.1 %. The tensile strength (55.95 MPa), impact strength (25.46 KJ/m2), flexural strength (140.65 MPa), elongation at break (38.6 %) of the EPM-3 composite material are 1.44, 2.74, 1.61, 1.89 times of EPM-0, respectively. Polycyclotriphosphazene-sulfone microspheres uniformly dispersed in the epoxy matrix and effectively improve the Tg and thermostability of the composites.